Teaching the Concept of pH from the Perspective of Scientific Thinking: An Exploratory Systematic Review - Pineda-Caro, Diana Yicela; Medina-Vargas, Óscar Julio; Falla-Rocha, Gabriela (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this article was to carry out an exploratory systematic review, in order to identify which teaching strategies have addressed the concept of pH at different school levels, from the perspective of scientific thought. For this, an information search was carried out in the Web of Science (WoS) and Google Scholar databases; the time interval was from 2010 to October 2020, identifying 17 documents, of which only 8 were related to the research topic. Subsequently, an analysis was carried out to identify if these were congruent with scientific thinking skills: asking questions, describing facts, establishing models and arguing. As a result of this review, it was identified that didactic strategies of an experimental type are the most popular ones. For the most part, the concept is approached from topics such as natural indicators, in other cases, electronic devices and software are used, which allow developing skills not only in the scientific field, but also in technology and mathematics. In all cases, there is an affinity for conducting experiments, mainly of the home type. Likewise, the abstract and material representations that students can develop by participating in these activities are analyzed. Another important aspect that must be strengthened is the argumentation and the correct appropriation of the concept, according to its current definition.